Incorporation of recombinant proteins into extracellular vesicles by Lactococcus cremoris - Tina Vida Plavec; Kristina Žagar Soderžnik; Giulia Della Pelle; Špela Zupančič; Robert Vidmar; Aleš Berlec (Scientific Reports)
Abstract Extracellular vesicles (EVs) are nanosized lipid bilayer particles released by various cellular organisms that carry an array of bioactive molecules. EVs have diagnostic potential, as they play a role in intercellular interspecies communication, and could be applied in drug delivery. In contrast to mammalian cell-derived EVs, the study of EVs from bacteria, particularly Gram-positive bacteria, received less research attention. This study aimed to investigate the production of EVs by lactic acid bacterium Lactococcus cremoris NZ9000 and to examine the impact of recombinant protein expression on their formation and protein content. Four different recombinant proteins were expressed in L. cremoris NZ9000, in different forms of expression and combinations, and the produced EVs were isolated using the standard ultracentrifugation method. The presence of vesicular structures (50–200 nm) in the samples was confirmed by transmission electron microscopy and by flow cytometry using membrane-specific stain. Mass spectrometry analyses confirmed the presence of recombinant proteins in the EVs fraction, with amounts ranging from 13.17 to 100%, highlighting their significant incorporation into the vesicles, together with intrinsic L. cremoris NZ9000 proteins that were either more abundant in the cytoplasm (ribosomal proteins, metabolic enzymes) or present in the membrane. The presence of the most abundant lactococcal proteins in EVs fraction suggests that protein cargo-loading of EVs in L. cremoris NZ9000 is not regulated. However, our data suggests that L. cremoris NZ9000 genetically engineered to express recombinant proteins can produce EVs containing these proteins in scalable manner. As L. cremoris NZ9000 is considered safe bacterium, EVs from L. cremoris NZ9000 could have several advantages over EVs from other bacteria, implying possible biotechnological applications, e.g. in therapeutic protein delivery.